Effects of a preseason intervention on anthropometric characteristics of semiprofessional rugby league players - Morgan, P. J.; Callister, R. (The Journal of Strength and Conditioning Research, 2011)
A player's physique and body composition can substantially influence performance in a rugby league; however, there is limited evidence about the impact of training on the anthropometric profile of rugby league players. The purpose of this study was to investigate the effects of a preseason training program on the anthropometric characteristics of semiprofessional players. Fifty-seven semiprofessional rugby league players (29 backs and 28 forwards) completed a range of anthropometric tests including stature, body mass, girths, breadths, lengths, and 9 skinfold sites at the beginning (late October) and end (mid February) of a 14-week preseason. with use of Lifesize software, values were calculated for fat mass, muscle mass, percent body fat, and somatotype. Analysis of change was conducted separately for forwards and backs. Over the preseason, both backs (p < 0.01) and forwards (p < 0.001) reduced fat mass, increased muscle mass (backs [p < 0.001]; forwards [p < 0.001]), and key upper-body girth measurements. Between group analyses indicated that forwards experienced significantly greater reductions in some skinfold sites (triceps [p < 0.05], subscapular [p < 0.05], abdominals [p < 0.05]), fat mass (p < 0.05) and overall percent body fat than backs (p < 0.05). These players were predominantly endomorphic-mesomorphs. A preseason training program that included testing and feedback, education, and a combination of resistance, speed, and cardiorespiratory training and resulted in considerable anthropometric improvements by semiprofessional players. Rugby league conditioning staff at a semiprofessional level should consider the value of a comprehensive structured and periodized preseason training program and aim to educate players about strategies to achieve body composition goals.